The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.neuroimage.2017.07.057
|View full text |Cite
|
Sign up to set email alerts
|

Subcortical and cortical correlates of pitch discrimination: Evidence for two levels of neuroplasticity in musicians

Abstract: Musicians are highly trained to discriminate fine pitch changes but the neural bases of this ability are poorly understood. It is unclear whether such training-dependent differences in pitch processing arise already in the subcortical auditory system or are linked to more central stages. To address this question, we combined psychoacoustic testing with functional MRI to measure cortical and subcortical responses in musicians and non-musicians during a pitch-discrimination task. First, we estimated behavioral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 81 publications
2
36
1
Order By: Relevance
“…For example, when playing piano, pressing a key to produce a certain pitch will, over time with practice, develop key-to-pitch mapping (Maes et al, 2014). Years of musical training enhance auditory mechanisms related to sub/cortical areas, not only in response to music, such as pitch perception (Kishon-Rabin et al, 2001;Schön et al, 2004;Zatorre et al, 2007;Barnett et al, 2017;Bianchi et al, 2017), but also to other AV events such as speech (Patel, 2011). With this basis, in the present study, the role of previous musical experience will be examined for N1 and P2 in AV music perception during which visual cues from finger and hand movement can offer prediction for the corresponding sound.…”
Section: Introductionmentioning
confidence: 99%
“…For example, when playing piano, pressing a key to produce a certain pitch will, over time with practice, develop key-to-pitch mapping (Maes et al, 2014). Years of musical training enhance auditory mechanisms related to sub/cortical areas, not only in response to music, such as pitch perception (Kishon-Rabin et al, 2001;Schön et al, 2004;Zatorre et al, 2007;Barnett et al, 2017;Bianchi et al, 2017), but also to other AV events such as speech (Patel, 2011). With this basis, in the present study, the role of previous musical experience will be examined for N1 and P2 in AV music perception during which visual cues from finger and hand movement can offer prediction for the corresponding sound.…”
Section: Introductionmentioning
confidence: 99%
“…While it has been shown that processing effort increases with increasing the processing demand of the listening condition for speech (Johnsrude and Rodd 2015 ), to the knowledge of the authors, this is the first study to investigate pupil dilation during a pitch discrimination task with varying harmonic resolvability and task difficulty. While in a previous study (Bianchi et al 2014 ), pupil dilations were measured for conditions with concomitantly varying harmonic resolvability and task difficulty, a new experimental design was used here to disentangle the effects of resolvability and task difficulty on pupil dilations. In experiment 2, pitch discrimination thresholds were measured behaviorally at three F0s (i.e., three levels of resolvability) and at three different points of the psychometric function (i.e., three levels of task difficulty).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are dedicated pitch perception areas in the cerebral cortex (Patterson et al, 2002;Puschmann et al, 2010;De Angelis et al, 2018), the IC has also been associated with the representation of pitch Chandrasekaran et al, 2012;Bianchi et al, 2017; reviewed in Gruters and Groh, 2012;Pannese et al, 2015). Thus, the IC might be a candidate structure for explaining altered vocal pitch perception in ASD.…”
Section: Discussionmentioning
confidence: 99%